Landowner response to wildfire risk: Adaptation, mitigation or doing nothing. (15th August 2015) - Gan, Jianbang; Jarrett, Adam; Gaither, Cassandra Johnson
Abstract: Wildfire has brought about ecological, economic, and social consequences that engender human responses in many parts of the world. How to respond to wildfire risk is a common challenge across the globe particularly in areas where lands are controlled by many small private owners because effective wildfire prevention and protection require coordinated efforts of neighboring stakeholders. We explore (i) wildfire response strategies adopted by family forestland owners in the southern United States, one of the most important and productive forest regions in the world, through a landowner survey; and (ii) linkages between the responses of these landowners and their characteristics via multinomial logistic regression. We find that landowners used diverse strategies to respond to wildfire risk, with the most popular responses being "doing nothing" and combined adaptation and mitigation, followed by adaptation or mitigation alone. Landowners who had lost properties to wildfire, lived on their forestlands, had a forest management plan, and were better educated were more likely to proactively respond to wildfire risk. Our results indicate the possibility to enhance the effectiveness of collective action of wildfire risk response by private forestland owners and to coordinate wildfire response with forest conservation and certification efforts. These findings shed new light on engaging private landowners in wildfire management in the study region and beyond. Highlights: Private forestland owners use diverse strategies in response to wildfire risk. Past wildfire loss and living on forestland provoke wildfire risk response. Education stimulates more comprehensive wildfire response action. Wildfire response can be coordinated with forest conservation and certification.